Whey protein isolate-dextran conjugates: Decisive role of glycation time dependent conjugation degree in size control and stability improvement of colloidal nanoparticles. (August 2021) - Liu, Qian; Cui, Heping; Muhoza, Bertrand; Hayat, Khizar; Hussain, Shahzad; Tahir, Muhammad Usman; Zhang, Xiaoming; Ho, Chi-Tang
Abstract: Whey protein isolate-dextran (WPI-dextran) conjugates were acquired via Maillard reaction for different durations (1–7 days) and their potential to govern the size and stability of colloidal nanoparticles formed from heating electrostatic complexes of WPI-dextran conjugates and chondroitin sulfates was assessed. The grafting degree and browning index gradually increased with the reaction time. The intensity of amide bands increased in the first 2 days and then declined. As the duration increased, the content of α-helix increased from 23.9% to 29.6%, while β-sheet and random coil decreased from 23.8% and 38.1% to 19.6% and 32.7%, respectively. Moreover, the surface hydrophobicity was reduced as the conjugation progressed, while surface and total sulfhydryl content gradually increased from 5.3 and 15.4 μmol/g to 11.0 and 17.9 μmol/g, respectively. Meanwhile, fluorescence intensity of conjugates decreased with prolonged durations. These changes with increasing grafting degree prompted greater steric hindrance, weakened hydrophobic interaction, and improved stability of protein during heating, thus facilitating the decreasing diameter of the corresponding heat-induced nanoparticles. In comparison with the nanoparticles derived from non-conjugated mixture of WPI and dextran, those from WPI-dextran conjugates showed an excellent stability to aggregation and dissociation upon synergistic influence of pH variation (1–10) and enhancing ionic strength (0–4 mol/L). Highlights: Conjugation degree of the conjugates depended on Maillard reaction time. Conjugation induced conformational changes of protein. Nanoparticles prepared from conjugates were insensitive to environmental changes. Size of nanoparticles can be tuned by glycation of protein. Steric hindrance promoted size control and stability of nanoparticles.